2007
DOI: 10.1038/sj.bmt.1705784
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory pseudotumor following hematopoietic stem cell transplantation: a new case and review of the literature

Abstract: Inflammatory pseudotumor (IPT) is a rare tumor that occurs in various organs and tissues. The clinical picture varies from the more frequent benign lesions to the rare malignant tumors with distant metastases. IPT associated with hematopoietic stem cell transplantation (HSCT) is rarely reported. In this article, we review the reports of IPT after HSCT and describe the first case of bladder IPT. We also review the possible factors involved in the pathogenesis. IPT might be rare but it is a potentially serious c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 18 publications
(29 reference statements)
0
8
0
Order By: Relevance
“…All of the six reported cases of IPT after SCT were treated with surgical resection and the aetiology was thought to be SCT related immunosuppression and prior chemotherapy [13]. In contrast, a case of retroorbital IPT in a patient with systemic lupus erythematosus was successfully treated with rituximab [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All of the six reported cases of IPT after SCT were treated with surgical resection and the aetiology was thought to be SCT related immunosuppression and prior chemotherapy [13]. In contrast, a case of retroorbital IPT in a patient with systemic lupus erythematosus was successfully treated with rituximab [10].…”
Section: Discussionmentioning
confidence: 99%
“…IPT have been reported to be successfully treated by surgery, chemotherapy, and immunosuppressive therapy with rituximab in a case of orbital IPT [1012]. There have been six cases of IPT diagnosed in patients after haematopoietic stem cell transplant (SCT) and one case of hepatic IPT in a pediatric patient before SCT with severe congenital neutropenia [13, 14]. To the best of our knowledge, ours is the first report of hepatic IPT in an adult who was due to undergo SCT.…”
Section: Introductionmentioning
confidence: 99%
“…To date, only six cases of IMTs after allogeneic HCT have been reported . Patients were aged 8–50 yr, and the primary diseases were AML (n = 3), ALL (n = 2), and ATL (n = 1).…”
Section: Discussionmentioning
confidence: 99%
“…Hepatic IMT has been reported after bone marrow and liver transplantation. 6,7 Here, a case of IMT of the liver following renal transplantation was first reported that implicated immunosuppression as one possible underlying factor of these rare lesions. /L, carcinoembryonic antigen (CEA) 1.9 ng/mL (normal 0.00-5.00), and alphafetoprotein (AFP) 9.7 ng/mL (normal 0.00-25.00).…”
Section: Introductionmentioning
confidence: 99%